Engineering lecturers' views on CLIL and EMI - Aguilar, Marta (International journal of bilingual education and bilingualism, 2017)
The present study aims to shed some light on how engineering lecturers teaching in English at a Spanish university view their work (teaching goals) within the current European internationalisation trend of offering courses and master programmes in English. A questionnaire where content and language integrated learning (CLIL) and English-medium instruction (EMI) were differentiated and with questions on their self-attributed duties, training preferences, assessment and internationalisation issues, among others, was prepared. The 41 lecturers who participated were asked to identify the modality they were following and their views related to the key factors in their courses. Findings point to the fact that EMI is the modality they follow and that they do not want to shift to CLIL because they refuse to teach language. To gain qualitative information about their beliefs, six lecturers were later interviewed. These interviews suggested that lecturers attach no importance to language integration. More specifically, they do not usually reflect on their lecturing, they welcome the idea of distinguishing both modalities in higher education (HE), they regard English proficiency as a key factor for all stakeholders and finally they think CLIL better suits less proficient students in HE.